Okapi at TREC-2 - Robertson, Stephen; Walker, S.; Jones, S.; Hancock-Beaulieu, M. M.; Gatford, M. (The Second Text REtrieval Conference (TREC-2), 1994)
The Okapi system comprises a search engine or basic search system (BSS), a low level interface used mainly for batch runs and a user interface for the manual search experiments, together with data conversion and inversion utilities. This paper reports on City University's work on the TREC-2 project from its commencement up to November 1993. It includes many results which were obtained after the August 1993 deadline for submission of official results.